Economic report of the President : transmitted to the Congress, January 1980 . Together with The annual report of the Council of Economic Advisers - United States President; Council of Economic Advisers (U.S.) (Washington [D.C.] : U.S. Goverment Printing Office, 1980)
The book covers the overview of the Economy in 1979, the economic outlook of 1980 - 1981, long-term policies for stability and growth and the world economy - testing resilience.
rpm 12/05/2017
Loans
Keywords: United States -- Economic policy; United States -- Economic conditions -- 1971-1981.